Organizational culture as the glue between people and organization: A competence-based view on learning and competence building - Jörg Freiling; Hanno Fichtner (Zeitschrift für Personalforschung (ZfP), 2010)
Is organizational culture a catalyst of competence development? This paper argues it is. The reason for this is that organizational culture fosters the process of learning and competence building and works as a glue between people and the organization they belong to. We employ a most recently developed approach belonging to market process theory, the so-called 'competence-based theory of the firm', to explain these causal relationships. – – Fördert Unternehmenskultur die Entwicklung organisationaler Kompetenzen? Dieser Beitrag bejaht die Frage mit Verweis auf die lernförderliche Wirkung von Unternehmenskultur. Die Unternehmenskultur stellt ein Bindeglied zwischen der personellen und organisationalen Ebene dar. Um die Wirkungsbeziehungen zwischen Unternehmenskultur und Kompetenzentwicklung zu untersuchen, bedient sich der Beitrag der jüngst auf marktprozesstheoretischer Basis entwickelten kompetenzbasierten Theorie der Unternehmung.
Keywords: 330; organizational culture; competence building; learning; Competence-based Theory of the Firm (CbTF); Unternehmenskultur; Lernen; Lernprozess; Wissensintensives Unternehmen; Theorie der Unternehmung